Diminished adrenal sensitivity to endogenous and exogenous adrenocorticotropic hormone in critical illness: a prospective cohort study. Issue 1 (December 2015) - de Jong, Margriet; Molenaar, Nienke; Beishuizen, Albertus; Groeneveld, AB
Abstract Introduction Adrenal dysfunction may represent critical illness-related corticosteroid insufficiency (CIRCI), as evidenced by a diminished cortisol response to exogenous adrenocorticotropic hormone (ACTH), but this concept and its clinical significance remain highly controversial. We studied the adrenal response to exogenous ACTH as a function of the endogenous cortisol-to-ACTH ratio, a measure of adrenal sensitivity, and of clinical variables, during critical illness and recovery from the acute phase. Methods We prospectively included 59 consecutive septic and nonseptic patients in the intensive care unit with treatment-insensitive hypotension in whom CIRCI was suspected; patients having received etomidate and prolonged corticosteroids were excluded. An ACTH test (250 μg) was performed, followed by a second test after ≥7 days in acute-phase survivors. Serum total and free cortisol, ACTH, and clinical variables were assessed. Patients were divided according to responses (delta, Δ) of cortisol to ACTH at the first and second tests. Results Patients with low (<250 nM ) Δ cortisol (n = 14 to 17) had higher baseline cortisol and ACTH but lower cortisol/ACTH ratios than patients with a normal Δ cortisol (≥250 nM ) in the course of time. A low Δ cortisol in time was associated with more-severe disease, culture-positive sepsis, and prolonged activated prothrombin time. Results for free cortisol were similar. Conclusions Even though the pituitary-adrenal axis is activated after stress during critical illness, diminished adrenal sensitivity to endogenous ACTH predicts a low increase of cortisol to exogenous ACTH, suggesting adrenal dysfunction, irrespective of the stage of disease. The data further suggest a role of disease severity and culture-positive sepsis.